2-Dimension rubik's cube game / Wan Mohd Afdzal Wan Harun - Wan Harun, Wan Mohd Afdzal (2009)
Rubik’s Cube, invented in the late 1970s by Erno Rubik of Hungary, is the most famous combinatorial puzzle of its time. The standard version of this puzzle is a 3x3x3 cube with different colors on each of the exposed squares of the subcubes or cubies. Every 3x3x1 plane of the cube can be rotated or twisted 90, 180 or 270 degrees relative to the rest of the cube. This will give a lot of advantages to the player that play this famous puzzle and solve it with optimal solution. The goal of this puzzle is to make sure that all the squares on each side of the cube are of the same color. To achieve this goal, the player needs to have a strategy. The beginner player needs to learn this strategy step by step and they need to understand why they need to do the step. The first problem that the beginner will face is, they are not able to see the whole cube. Human being only can see 50% of the cube in one time. The beginner player always make mistake in movement that will affect the other color that already complete or in other hand, the color in the right place. This happened because they have the first problem. This is why the researcher tries to develop 2Dimension rubik cube game. This game will present rubik’s cube in 2D, this will help beginner to solve their first problem. To make movement, the player needs to click the button. This game has 18 movement buttons. The button are Right1, Right2, Right3,Left1, Left2, Left3,Up1, Up2, Up3,Down1, Down2, Down3, Right4, Right5, Right6,Left4, Left5 and Left6. To save all the face, the researcher used 2D array to save all the color one by one. So this game needs 6 2D arrays because the rubik’s cube has 6 faces.